Risk factors and obstetric complications of large for gestational age births with adjustments for community effects: results from a new cohort study - Cameron Cate M; Spinks Anneliese B; Olog Adriana; Ng Shu-Kay; Searle Judy; McClure Rod J (BMC, 2010)
Abstract Background High birth weight has serious adverse impacts on chronic health conditions and development in children. This study identifies the social determinants and obstetric complications of high birth weight adjusted for gestational age and baby gender. Methods Pregnant women were recruited from three maternity hospitals in South-East Queensland in Australia during antenatal clinic visits. A questionnaire was completed by each participant to elicit information on eco-epidemiological exposures. Perinatal information was extracted from hospital birth records. A hierarchical mixture regression model was used in the analysis to account for the heterogeneity of birth weights and identify risk factors and obstetric complications of births that were large for gestational age. A generalized linear mixed model was used to adjust for (random) "community" effects. Results Pre-pregnancy obesity (adjusted OR = 2.73, 95% CI = 1.49-5.01), previous pregnancy (adjusted OR = 2.03, 95% CI = 1.08-3.81), and married mothers (adjusted OR = 1.85, 95% CI = 1.00-3.42) were significantly associated with large for gestational age babies. Subsequent complications included the increased need for delivery by caesarean sections or instrumental procedures (adjusted OR = 1.98, 95% CI = 1.10-3.55), resuscitation (adjusted OR = 2.52, 95% CI = 1.33-4.79), and transfer to intensive/special care nursery (adjusted OR = 3.76, 95% CI = 1.89-7.49). Communities associated with a higher proportion of large for gestational age births were identified. Conclusions Pre pregnancy obesity is the principal modifiable risk factor for large for gestational age births. Large for gestational age is an important risk factor for the subsequent obstetric complications. The findings improve the evidence-base on which to base preventive interventions to reduce the impact of high birth weight on maternal and child health.